2018
DOI: 10.1002/esp.4405
|View full text |Cite
|
Sign up to set email alerts
|

Sediment accumulation in embayments controlled by bathymetric slope and wave energy: Implications for beach formation and persistence

Abstract: High energy, rocky coastlines often feature sandy beaches within headland‐bound embayments. Not all such embayments have beaches however, and beaches in embayments can be removed by storms and may subsequently reform. What dictates the presence or absence of an embayed beach and its resilience to storms? In this paper, we explore the effect of offshore slope and wind conditions on nearshore sediment transport within idealised embayments to give insight into nearshore sediment supplies. We use numerical simulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Through numerical modelling, Preston et al (2018) investigated the role of slope and wave energy in nearshore morphodynamics. They showed that for an embayed beach, shoreface slope exerted a control on beach recovery.…”
Section: Drivers Of Shoreface Morphology 821 Lower Shorefacementioning
confidence: 99%
See 1 more Smart Citation
“…Through numerical modelling, Preston et al (2018) investigated the role of slope and wave energy in nearshore morphodynamics. They showed that for an embayed beach, shoreface slope exerted a control on beach recovery.…”
Section: Drivers Of Shoreface Morphology 821 Lower Shorefacementioning
confidence: 99%
“…"bathymetric slope is a major control on the nearshore sediment budget under calm climatic conditions". However, during storms, hydrodynamics seem to have more control over sediment loss than the slope (Preston et al, 2018).…”
Section: Drivers Of Shoreface Morphology 821 Lower Shorefacementioning
confidence: 99%
“…Coasts are dynamic, complex systems and their features are constantly changing because of both natural and human factors (Kurt et al, 2010;Ponte Lira et al (2016)). The natural processes that induce such changes include, amongst others, sea level variations due to global warming, wave climate alterations and coastal drift (Schnack et al, 2002;Caires et al, 2006;Stanica and Ungureanu, 2010;Hemer et al, 2013;IPCC, 2014;Dabrio and Polo, 2015;Johnson et al, 2015;Preston et al, 2018;Glavovic et al, 2019). The transformations to them that human activities can result in are, in many cases, irreparable.…”
Section: Introductionmentioning
confidence: 99%
“…Preston et al . () investigated how sediment accumulation in embayments can be affected by local bathymetry and available wave energy. Their work showed the profound implications for general beach formation and endurance of any beach that may form within a coastal compartment.…”
mentioning
confidence: 99%
“…The onshore moving bars were also shown to be narrower and steeper as they migrated onshore, mirroring wave shoaling, with results highlighting the importance of characterizing nearshore bars as a three-dimensional (3D) system. Preston et al (2018) investigated how sediment accumulation in embayments can be affected by local bathymetry and available wave energy. Their work showed the profound implications for general beach formation and endurance of any beach that may form within a coastal compartment.…”
mentioning
confidence: 99%